2005
DOI: 10.1111/j.1740-0929.2005.00246.x
|View full text |Cite
|
Sign up to set email alerts
|

Linkage mapping of four chicken calpain genes

Abstract: Calpains are intracellular Ca 2 + -dependent proteases and enzymes that contribute to growth and meat quality. In the present study, we identified polymorphisms in four calpain genes ( CAPN1 , CAPN2 , CAPN3 , and CAPN1.5 ) expressed ubiquitously in chicken using polymerase chain reaction-restriction fragment length polymorphism, and mapped them using two backcross families (East Lansing (EL) and Kobe University (KU)). CAPN2 and CAPN1.5 mapped to two locations on chromosome 3 about 30 cM apart, while CAPN3 mapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…1997). Okumura et al. (2005) identified four calpain genes ( CAPN1 , CAPN2 , CAPN3 and CAPN1.5 ) expressed ubiquitously in chicken.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1997). Okumura et al. (2005) identified four calpain genes ( CAPN1 , CAPN2 , CAPN3 and CAPN1.5 ) expressed ubiquitously in chicken.…”
Section: Introductionmentioning
confidence: 99%
“…Calpain is a ubiquitous cytoplasmic cysteine protease and its activity is absolutely dependent on calcium (Sorimachi et al 1997). Okumura et al (2005) identified four calpain genes (CAPN1, CAPN2, CAPN3 and CAPN1.5) expressed ubiquitously in chicken. Among them CAPN1 requires calcium at micromolar concentrations for activity and, for CAPN2, calcium at milimolar concentrations is needed (Suzuki & Sorimachi 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Okumura et al . (2005) identified polymorphisms in four calpain genes expressed in chicken (µ‐calpain gene, CAPN1 ; m‐calpain gene, CAPN2 ; p94 gene, CAPN3 ; and µ/m‐calpain, CAPN1.5 ), and mapped them using two backcross families.…”
Section: Introductionmentioning
confidence: 99%
“…We also analyzed the genetic constitution, genetic variability, and relation among the chicken populations using these loci. As the CAPN2 and CAPN1.5 are linked with about 20 cM on chicken chromosome 3 (Okumura et al . 2005), genotypes for these loci were treated as haplotype.…”
Section: Introductionmentioning
confidence: 99%
“…The calpains were discovered because the Z-disks in the muscle strips incubated in a Ca 2+ -containing solution disappeared in the absence of other ultrastructurally detectable changes (Dayton et al, 1981). Four calpain genes (i.e., μ-calpain gene, CAPN1; m-calpain gene, CAPN2; p94 gene, CAPN3; and μ/m-calpain, CAPN1.5) are expressed ubiquitously in chickens (Okumura et al, 2005). Among the calpain family members, CAPN1 degrades myofibrillar proteins under postmortem conditions and appears to be the primary enzyme in the postmortem tenderization process (Koohmaraie, 1992(Koohmaraie, , 1994(Koohmaraie, , 1996.…”
Section: +mentioning
confidence: 99%